THE EFFECT, IMPORTANCE AND FUNCTIONS OF MUSIC IN CINEMA:: EXAMPLE OF CAHIT BERKAY IN THE CONTEXT OF TURKISH CINEMA - Dolunay, Ayhan; Kasap, Fevzi; Kambur, Hüseyin (Revista Gênero e Interdisciplinaridade, 2021)
This study focuses on an example of Cahit Berkay who has an important place in the context of film music and the importance, effect and functions of music in the Turkish Cinema. Essentially of the study within the frame of literature review, music, cinema, the relation between music and the field of arts, Turkish Cinema and music, also provides information relates with Cahit Berkay in the context of music in Turkish cinema. The research part of the study, to measure the effects of the soundtracks composed by Cahit Berkay, “Selvi Boylum ve Al Yazmalım” and “Çöpçüler Kralı” movies detected by sample for purpose, versions separated from music with technical method and original music versions interview group (limited to Near East University Vocational School of Health Services Year 2 students) viewed; reactions of students, content analysis technique a from qualitative and quantitative research methods, has been measured within the framework of their responses through written opinion forms with predetermined structured questions. Furthermore, a semi-structural interview technique used from qualitative research methods, face to face interview performed with Cahit Berkay pre-prepared open-ended questions; the collected data have been evaluated by content analysis method.